2019
DOI: 10.1002/uog.20116
|View full text |Cite
|
Sign up to set email alerts
|

Role of fetal intertwin difference in middle cerebral artery peak systolic velocity in predicting neonatal twin anemia–polycythemia sequence

Abstract: Objectives To evaluate the relationship between the fetal intertwin difference in middle cerebral artery peak systolic velocity (MCA-PSV) and intertwin difference in hemoglobin (Hb) concentration at birth in monochorionic diamniotic (MCDA) twin pregnancies in order to assess its potential role in the prediction of twin anemia-polycythemia sequence (TAPS). MethodsThis was a retrospective cohort study of MCDA twin pregnancies delivered between January 2012 and January 2018. All pregnancies with measurements of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
(28 reference statements)
1
26
0
1
Order By: Relevance
“…The primary search of the Pubmed, Embase, and SCOPUS databases produced 432 publications. Based on abstract review, 54 of these publications were selected to be reviewed in their entirety [1,2,4,5,7,[9][10][11][12]16,19,. The secondary search of bibliographies produced three additional publications which were also reviewed in their entirety for a total 57 publications [6,66,67].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary search of the Pubmed, Embase, and SCOPUS databases produced 432 publications. Based on abstract review, 54 of these publications were selected to be reviewed in their entirety [1,2,4,5,7,[9][10][11][12]16,19,. The secondary search of bibliographies produced three additional publications which were also reviewed in their entirety for a total 57 publications [6,66,67].…”
Section: Resultsmentioning
confidence: 99%
“…The publications are detailed in Table 1 and reasons for exclusion are summarized in Figure 1. Five of the 57 publications, all from the primary search, described a study of MCDA twins where serial ultrasounds with MCA-PSV values were collected to detect TAPS with direct comparison to Hb values [5,9,10,19,47]. After applying QUADAS II methodology to these five studies, four were determined highly likely to have bias in patient selection ( Figure 2) [5,9,10,47].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tollenaar et al found that an MCA PSV delta of >0.5 MoM had a higher sensitivity and negative predictive value in diagnosing TAPS antenatally than the traditional cut-off of >1.5 and <1.0 MoM [14]. Moreover, Tavares De Sousa et al reported that a delta of >0.373 MoM was in fact the most optimal predictor of twin Hb discordance of >90th centile at birth [15]. A recent consensus using the Delphi procedure has focused on alleviating heterogeneity and achieving a uniform diagnostic criteria for TAPS.…”
Section: Introductionmentioning
confidence: 99%